2012
DOI: 10.1155/2013/528471
|View full text |Cite
|
Sign up to set email alerts
|

Study on Individual PAHs Content in Ultrafine Particles from Solid Fractions of Diesel and Biodiesel Exhaust Fumes

Abstract: In order to characterize PAHs emissions of diesel engine fuelled with diesel and its blend (B20, B40). In the particle phase, PAHs in engine exhausts were collected by fiberglass filters using Electrical Low Pressure Impactor (ELPI) and then determined by a high performance liquid chromatography with a fluorimetric detector (HPLC-FL). The main content in exhaust gases from diesel engine, regardless the type of applied fuel, is constituted by the particles fraction of diameter <0.25 μm. Particles sized <0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…2 has presented the average distribution of total PAHs adsorbed on the ultrafine particles in gasoline and diesel exhaust fumes. Particles with a diameter below 0.25 µm were mainly detected in the diesel exhaust, which confirmed our earlier results [11]. The average sizes of particles emitted in gasoline exhaust were smaller than particles emitted in diesel exhaust under similar operating conditions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2 has presented the average distribution of total PAHs adsorbed on the ultrafine particles in gasoline and diesel exhaust fumes. Particles with a diameter below 0.25 µm were mainly detected in the diesel exhaust, which confirmed our earlier results [11]. The average sizes of particles emitted in gasoline exhaust were smaller than particles emitted in diesel exhaust under similar operating conditions.…”
Section: Resultssupporting
confidence: 91%
“…During recent decades, continuous concern has been raised with respect to PM emitted during the operation of motor vehicles, mainly by diesel engines [7][8][9][10][11][12][13]. The World Health Organization (WHO) has reported that diesel engine exhaust is classified as carcinogenic to humans [14].…”
mentioning
confidence: 99%
“…There is an increasing concern about the chemical characterization of environmental samples of size-segregated samples [1][2][3]. This leads to the analysis of reduced sample sizes of particulate matter (PM) containing very low levels of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…These extractions are expensive in instrument and maintenance. Due to lower equipment cost and ease of operation, extraction by US stands as an attractive alternative 2 Journal of Chemistry [3,8]. Hence, procedures based on reducing sample size and solvent requirements have been developed to achieve a miniaturization strategy for US extraction [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their low water solubility and high lipophilicity, PAHs are easily and rapidly absorbed by organisms and can be accumulated in aquatic organism or adsorbed onto the surface of suspended matter, get deposited on the sea floor and be passed onto the marine food chain. Sources of PAHs can be either petrogenic, from petroleum-related activities or pyrogenic (pyrolytic), from the incomplete combustion of diesel fuel and engine oil (16) wood, coal, biomass of forest, grass fires, waste incinerators, and fossil fuels that are used in industrial operations and power plants (17) . Inlet and outlet water of (SOPC) is located in Zietyia area about 2-3 km south west of Suez city and close to the most important and famous international way ) Fig.…”
mentioning
confidence: 99%